Anatomical Variations in the Brachial Plexus Implications for Surgical Interventions - Sonia Umar Afridi,Toqeer Ahmed Iqbal,Kaukab Anjum, Madiha Ali, Sadia Shaukat , Mohammad Saad Abdullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Brachial plexus is a nerve plexus of the upper limb: the issue of anatomical variation as a risk factor in surgery. It is crucial to comprehend all these differences in the human body because they help reduce risks related to surgeries in the neck, shoulder, as well as upper limb.  Objectives: to examine the anatomical differences in the brachial plexus of 150 patients for more effective procedures in the operation theatre.